Pengaruh Pembinaan Keagamaan oleh Samanera dan Atthasilani Terhadap Perilaku Keagamaan Umat Buddha di Malang Raya - Kadek Yudi Murdana (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
This study aimed to determine the influence of religious formation by Samanera and Atthasilani on Buddhist religious behavior in Malang Raya. The approach used in this research is quantitative research with the type of research included in the survey research. The results showed that religious guidance has a significant influence on Buddhist religious behavior in Malang Raya, can be proved from correlation value 0.724 or 72.4% and significant with 0.000 value. This shows that there is a significant influence between the variables of religious development on Buddhist religious behavior in Malang Raya.